Bacterial community composition of internal circulation reactor at different heights for large-scale brewery wastewater treatment. (July 2021) - Chen, Junfeng; Liu, Yanyan; Liu, Kai; Hu, Lijun; Yang, Jiaqi; Wang, Xuemei; Song, Zhi-ling; Yang, Yuewei; Tang, Meizhen; Wang, Renjun
Graphical abstract: Highlights: Bacterial community was analyzed in IC reactor for brewery wastewater treatment. Proteobacteria, Bacteroidetes, Chloroflexi were dominant phyla in IC reactor. Longilinea, Desulfomicrobium, Caldithrix and Geobacter were abundant genera. COD and BOD removal efficiency of IC reactor were > 80% for brewery wastewater. Abstract: This study analyzed bacterial community structure for large-scale brewery wastewater treatment at different heights in internal circulation (IC) reactor. Proteobacteria, Bacteroidetes and Chloroflexi were dominant bacteria, which accounted for 64.17%, 64.04%, 59.87% and 55.79% in phylum level, respectively. The unidentified bacteria were accounted for a large proportion in genus level, available data showed that Longilinea, Desulfomicrobium, Caldithrix, Geobacter and Syntrophorhabdus were relatively abundant. Organic fermentation, hydrolysis, and acidification were mainly completed at the bottom, and production of hydrogen and methane were completed in the upper and middle part of reactor. Alpha diversity and cluster distance analysis showed the bacterial community could be divided into bottom, middle and upper part of IC reactor. The IC reactor possessed the CODCr removal efficiency of 80% − 84.09%, and BOD5 of 77.50% − 86% for brewery wastewater. This study would provide bacterial analysis references of IC reactor for industrial wastewater treatment in future.